La violence politique dans le périodique satirique Simplicisssimus de l’avant à l’après Première Guerre mondiale - Pascale Cohen-Avenel (Amnis)
Political violence is particularly present between 1919 and 1923 in Simplicissimus, which was the most famous, and indeed the best, satirical magazine in Germany at the beginning of the 20th century. This violence is especially present in the images caricaturing the occupation of the Rhineland, and subsequently of the Ruhr, by French-African troops, and the referendum on self-determination in Silesia, as well as the Revolution of 1918, the clashes between the different political parties and the aborted putsches of 1920 and 1923, and the wars being waged during this period elsewhere in the world, notably in China and Japan. At the same time, these images hark back to the representations of violence in the pre-WWI period, both in Germany, which was the victim of Prussian oppression, and abroad, with the wars in the Balkans. If violence is generated by war, the First World War is just one example of this phenomenon among many. As far as the German Expressionists are concerned, however, it was their direct exposure to war that marked the end of their fascination with violence.